2015
DOI: 10.1056/nejmoa1414905
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Assessment of Rapid Endovascular Treatment of Ischemic Stroke

Abstract: This article is available at e-publications@RCSI: http://epubs.rcsi.ie/gerstrmedart/1 -Use LicenceThis work is licensed under a Creative Commons Attribution-Noncommercial-Share Alike 4.0 License.This article is available at e-publications@RCSI: http://epubs.rcsi.ie/gerstrmedart/1T h e ne w e ngl a nd jou r na l o f m e dicine n engl j med nejm.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

110
3,798
22
116

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 5,300 publications
(4,046 citation statements)
references
References 37 publications
110
3,798
22
116
Order By: Relevance
“…2015; Goyal et al. 2015). Our analysis did not show a significant interaction of reperfusion and collaterals on outcome, that is, the effect of reperfusion on outcome seemed to be independent of the collaterals rated on CTA.…”
Section: Discussionmentioning
confidence: 99%
“…2015; Goyal et al. 2015). Our analysis did not show a significant interaction of reperfusion and collaterals on outcome, that is, the effect of reperfusion on outcome seemed to be independent of the collaterals rated on CTA.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the size of the lesion to potentially promote better functional outcomes is the driving force behind interventions such as intravenous tissue plasminogen activator8 and mechanical embolectomy 9. However, most studies have indicated that the correlation between infarct volume and functional outcomes are only moderate,7, 10 if related at all 4, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was shown that intra‐arterial treatment (IAT) is highly effective in patients with acute ischemic stroke caused by a proximal intracranial arterial occlusion, and it has revolutionized stroke treatment 1, 2, 3, 4, 5, 6…”
mentioning
confidence: 99%